PENGARUH BIAYA LINGKUNGAN DAN KINERJA LINGKUNGAN TERHADAP PROFITABILITAS PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - Annas Lalo; Muhammad Irwan Nur Hamiddin (Universitas Sains dan Teknologi Komputer, 2021)
The Effect of Environmental Costs and Environmental Performance on Profitability in Manufacturing Companies Listed on the Indonesia Stock Exchange The purpose of This study is to examine and analyze the effect of (i) environmental costs on profitability, and (ii) environmental performance on profitability in manufacturing companies listed on the Indonesia Stock Exchange in the 2019-2020 period. Data collection uses secondary data obtained from the annual report published by the Indonesia Stock Exchange. The population in this study are manufacturing companies listed on the Indonesia Stock Exchange and participating in PROPER in the 2019-2020 period. The sampling technique used was purposive sampling. The data analysis method is in the form of quantitative analysis using multiple linear analysis and hypothesis testing using software E